Internal audit effectiveness : a case study on Mota-Engil - Queirós, Ana Filipa Coelho (2021)
The present report evolved as a result of the opportunity of a curricular internship that took place in the Internal Audit department of Mota-Engil SGPS, from September 2, 2019, to February 28, 2020. The purpose of the current study is to analyse the effectiveness of the internal audit function of Mota-Engil SGPS. In particular, this study focuses on four main determinants: positioning, planning, resources and processes. This study also sought to, based on the best practices described in the literature and the activity on both Portuguese and European construction organizations, to present some suggestions that may improve the effectiveness of the internal audit department. A case study approach was adopted to investigate the Internal Audit department of Mota-Engil SGPS. The data was collected through a participant observation and documentation analysis. Also, this study incorporates a survey to the Portuguese organizations listed on the PSI-20 and the European construction organizations listed on the ENR Top 250 Global Contractors of 2019, to understand the internal audit practices among the main peers of Mota-Engil and strengthened the recommendations provided. During the internship I not only recognized a misalignment between the formal standards adopted by the department and the actual practices, but also identified some areas with opportunities for improvement. Therefore, based on the best practices described in the literature and the answers from the benchmark survey performed to the to the main peers of the Group Mota-Engil, I suggest an optimization of the risk-based internal audit plan, the definition of a goal for the auditable universe of the Group, an investment in IT skills, the integration data analytics across the entire audit process and the implementation of all the components of the QA&IP. I believe these recommendations will increase the effectiveness of internal audit department of Mota-Engil SGPS and enhance the value added to the Group.